#TITLE_ALTERNATIVE# - M. (NIM 13204192), SIRIUS
lndustry has widely used Modern Predictive Controlalgorithm (MPC). MPC imple-mentation needs a high specification hardware system such as a personal computer. MPC implementation on lower specification hardware brings more benefits to the industrialuser. Programmable Logic Controller (PLC) is a simple hardware system which has been widely used on industry. PLC-based implementation of MPC brings more efficiency and effectiveness on industry. This problem has been solved by finishing this Final Project. This MPC algorithm implementation on PLC is purposed to improve transient and steady-state response of a simple plan system. The plan system is a simple DC motor. The result of MPC on PLC is compared with other control algorithms, which are also already implemented on PLC. These algorithms are Proportional-lntegral-Derivative (PlD) and PlD anti-wind-up. At the beginning, learning PLC's and DC motor's characteristics and specifications is done. After that, MPC, PlD, and PlD anti-wind-up are simulated on MATLAB software. Next, the implementation of MPC, PlD, and PlD anti-wind-up are programmed on PLC. The result of these three control algorithm, simulation and implementation, iscompared and analyzed.